The Place of Law in Society - Tokhtayev Sardor Sultan ugli (Zien Journals, 2021)
Today, the sphere of law is also the most important system of society. First of all, this sphere of development is an important base for the rise and development of society. As the state grows developed, various inequalities may arise and the most alternative way to overcome such shortcomings is the development of this legal system.
Keywords: Law; Kostitutsy; Problems; Society